Ordering, pricing, and lead-time quotation under lead-time and demand uncertainty - WU, Zhengping (Institutional Knowledge at Singapore Management University, 2012)
In this article, we study the newsvendor problem with endogenous setting of price and quoted lead-time. This problem can be observed in situations where a firm orders semi-finished product prior to the selling season and customizes the product in response to customer orders during the selling season. The total demand during the selling season and the lead-time required for customization are uncertain. The demand for the product depends not only on the selling price but also on the quoted lead-time. To set the quoted lead-time, the firm has to carefully balance the benefit of increasing demand as the quoted lead-time is reduced against the cost of increased tardiness. Our model enables the firm to determine the optimal selling price, quoted lead-time, and order quantity simultaneously, and provides a new set of insights to managers.